A Case of Filiform Wart Effectively Treated with Calcarea carbonica - Garg, Khushboo (Homœopathic Links, 2024)
Warts are skin growths that are benign (noncancerous) and develop on different parts of the body. These are caused by Human Papilloma Viruses (HPV). Warts are more prevalent in children and teenagers but can affect anyone at any age. Over time, the body's immune system frequently succeeds in battling the viruses, and the warts eventually vanish by themselves. However, people with compromised immune systems may find it considerably harder. Conventional treatment mostly consists of methods such as topical treatments, cryotherapy, ablation, and so on, which may have a variety of adverse effects. The likelihood of recurrence is also high. Here comes the scope of individualized homoeopathic treatment that directs and stimulates the body's self-regulatory mechanisms to restore its natural equilibrium in a cost-effective manner. A casereport of a 20-year-old woman with filiform warts on the scalp is presented here. Calcarea carbonica 200 was prescribed as per the homoeopathic principles which was repeated in 1 M potency. The case was followed up fortnightly. The warts disappeared completely after homoeopathic treatment without the use of any topical applications along with marked improvement in other associated complaints. The total score was 10 on Monarch inventory assessment and +3 on ORIDL (outcome in relation to impact on daily living), suggesting improvement in the overall well-being of the patient. This case report suggests that filiform warts can be successfully treated with individualized homoeopathic medications.
Keywords: filiform wart; homoeopathy; repertorization; Calcarea carbonica; modified Naranjo algorithm; ORIDL